MLOps with AWS App Runner - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn to use AWS App Runner to do an MLOps workflow that deploys a Flask Microservice that running sklearn. This tutorial walks you through how to deploy code from the O'Reilly book Practical MLOps using the AWS App Runner Service. Topics include: * MLOps * AWS App Runner * Container as a Service * Python * Flask * Microservice * Sklearn * Machine Learning Engineering.